2018
DOI: 10.1186/s13006-018-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delayed initiation of breastfeeding: a cross-sectional study in South Sudan

Abstract: BackgroundThe global breastfeeding recommendation states that all infants should be put to the breast within one hour of birth, which is defined as timely initiation or early initiation of breastfeeding. Early initiation of breastfeeding is associated with reduced risk in infant illness and death. Understanding the determinants of delay in initiation of breastfeeding might spur health staff and policy makers to foster timely breastfeeding. We assessed the prevalence and determinants of delay in initiation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 35 publications
9
26
3
Order By: Relevance
“…The odds of colostrum avoidance among mothers who have exposure to infant formula advertisement were nearly seven times, (AOR = 7.476, 95% CI: 3.549, 15.752), higher than the counterpart. The study is in line with report from South Sudan [33]. Infant formula advertising has weakened breastfeeding and misled mothers to discard colostrum and to adopt prelacteal feed for their children.…”
Section: Discussionsupporting
confidence: 88%
“…The odds of colostrum avoidance among mothers who have exposure to infant formula advertisement were nearly seven times, (AOR = 7.476, 95% CI: 3.549, 15.752), higher than the counterpart. The study is in line with report from South Sudan [33]. Infant formula advertising has weakened breastfeeding and misled mothers to discard colostrum and to adopt prelacteal feed for their children.…”
Section: Discussionsupporting
confidence: 88%
“…The same results had been found in our nationally representative samples [19]. A similar observation was also mentioned by several studies [36][37][38][39][32][33][34]. This study found that mothers aged 20-34 years were more likely to provide EIBF to their children than mothers aged 35 years and above.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of EIBF among mothers in Rajshahi district was also higher than south Asian countries like India (21%) [28], Pakistan (8.5%) [29], other developing countries like Nigeria (34.7%) [30], Iran (32.2%) [31] and South Sudan (48%) [32]. The rate of EIBF of mothers in Ethiopia was close (83.7%) to our nding [33].…”
Section: Discussionsupporting
confidence: 59%
“…At the same time, in low- middle-income countries, it ranged from 35% in the Middle East and North Africa to 65% in Eastern Southern Africa regions [ 2 ]. Prevalence in African countries varies from 34.7% in Nigeria and 87.2% in Sudan [ 8 13 ].…”
Section: Introductionmentioning
confidence: 99%